2019
DOI: 10.7759/cureus.4941
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Catastrophe during Benign Mediastinal Tumor Mass Excision: A Case Report

Abstract: Mature teratoma of the mediastinum poses a significant surgical challenge due to close vicinity to vital structures causing respiratory insufficiency or hemodynamic compromise. While the malignant variety of germ cell tumors (GCT) generally present with florid symptoms, benign teratomas are detected incidentally on imaging. Large teratomas presenting as mediastinal mass syndrome have additional difficulty in airway access. Herein, we report a case of a 40-year-old-female with no significant comorbidities prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Some cysts are known to cause specific symptoms related to their structure, location, and formation mechanisms. 4 Our patients also had pressure on some mediastinal organs and related symptoms. Seven of our patients had trachea compression and associated cough and shortness of breath.…”
Section: Discussionmentioning
confidence: 58%
“…Some cysts are known to cause specific symptoms related to their structure, location, and formation mechanisms. 4 Our patients also had pressure on some mediastinal organs and related symptoms. Seven of our patients had trachea compression and associated cough and shortness of breath.…”
Section: Discussionmentioning
confidence: 58%
“…General anesthetics and muscle relaxants decrease chest wall muscle tone, elevate the diaphragm, change the position of the tumor, and increase the risk of pressure obstruction of the airways and great blood vessels [1]. Furthermore, increased intrathoracic pressure due to positive pressure ventilation after intubation may worsen airway obstruction, resulting in further respiratory failure and circulatory collapse [2,3]. In such cases, extracorporeal membrane oxygenation (ECMO) should be provided in conjunction with general anesthesia [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the proximity of a mediastinal mass to vital structures in the mediastinum can make the operation and anesthesia considerations more technically challenging. 2,13 If a mass is larger, it is more likely to be abutting major structures and thus causing symptoms (for example, a mass compressing the lung causing shortness of breath or a mass abutting the esophagus causing dysphagia). Larger mediastinal masses may be more technically challenging to resect, thus leading to a longer postoperative length of stay.…”
Section: Discussionmentioning
confidence: 99%